Angiotensin‐converting enzyme inhibition prevents myocardial infarction‐induced increase in renal cortical cGMP and cAMP phosphodiesterase activities. (25th May 2015) - Clauss, François; Charloux, Anne; Piquard, François; Doutreleau, Stéphane; Talha, Samy; Zoll, Joffrey; Lugnier, Claire; Geny, Bernard
Abstract We investigated whether myocardial infarction (MI) enhances renal phosphodiesterases (PDE) activities, investigating particularly the relative contribution of PDE1‐5 isozymes in total PDE activity involved in both cGMP and cAMP pathways, and whether angiotensin‐converting enzyme inhibition (ACEi) decreases such renal PDE hyperactivities. We also investigated whether ACEi might thereby improve atrial natriuretic peptide (ANP) efficiency. We studied renal cortical PDE1‐5 isozyme activities in sham (SH)‐operated, MI rats and in MI rats treated with perindopril (ACEi) 1 month after coronary artery ligation. Circulating atrial natriuretic peptide (ANP), its second intracellular messenger cyclic guanosine monophosphate (cGMP) and cGMP/ANP ratio were also determined. Cortical cGMP‐PDE2 (80.3 vs. 65.1 pmol/min/mg) and cGMP‐PDE1 (50.7 vs. 30.1 pmol/min/mg), and cAMP‐PDE2 (161 vs. 104.1 pmol/min/mg) and cAMP‐PDE4 (307.5 vs. 197.2 pmol/min/mg) activities were higher in MI than in SH rats. Despite increased ANP plasma level, ANP efficiency tended to be decreased in MI compared to SH rats. Perindopril restored PDE activities and tended to improve ANP efficiency in MI rats. One month after coronary ligation, perindopril treatment of MI rats prevents the increase in renal cortical PDE activities. This may contribute to increase renal ANP efficiency in MI rats.